The Effect of Bilateral Orchiectomy on Total Prostate Specific Antigen (TPSA) Levels in Prostate Adenocarcinoma Patients - Sp.U, WIKAN KURNIAWAN (Rumah Sakit Akademik Universitas Gadjah Mada, 2024)
AbstractBackground: Hormonal therapy is one treatment option for prostate cancer. There are two main categories of hormone therapy: surgical therapy and non-surgical therapy. Orchiectomy is the surgical method of hormone therapy; medication supplementation is the non-surgical method. Many kinds of indicators are used to track the advancement of patients with prostate cancer receiving hormone therapy. tPSA levels are one of the markers that are regularly evaluated.Methods: In this retrospective study, PSA levels in patients with prostate adenocarcinoma cancer were evaluated before and after bilateral orchiectomy. Use the search terms